Transient photoinduced ‘hidden’ phase in a manganite - Ichikawa, Hirohiko; Nozawa, Shunsuke; Sato, Tokushi; Tomita, Ayana; Ichiyanagi, Kouhei; Chollet, Matthieu; Guerin, Laurent; Dean, Nicky; Cavalleri, Andrea; Adachi, Shin-ichi; Arima, Taka-hisa; Sawa, Hiroshi; et al. (Nature materials, 2011)
The control over phase transitions in complex oxides offers the possibility to control their electronic and structural properties. The discovery of a new route to ultrafast photoswitching of manganites via high-energy ‘hidden’ excited states offers the possibility of phase transitions free from thermal effects. Photoinduced phase transitions are of special interest in condensed matter physics 1 , 2 because they can be used to change complex macroscopic material properties on the ultrafast timescale. Cooperative interactions between microscopic degrees of freedom greatly enhance the number and nature of accessible states, making it possible to switch electronic, magnetic or structural properties in new ways 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 . Photons with high energies, of the order of electron volts, in particular are able to access electronic states that may differ greatly from states produced with stimuli close to equilibrium 10 . In this study we report the photoinduced change in the lattice structure of a charge and orbitally ordered Nd 0.5 Sr 0.5 MnO 3 thin film using picosecond time-resolved X-ray diffraction. The photoinduced state is structurally ordered, homogeneous, metastable and has crystallographic parameters different from any thermodynamically accessible state. A femtosecond time-resolved spectroscopic study shows the formation of an electronic gap in this state. In addition, the threshold-like behaviour and high efficiency in photo-generation yield of this gapped state highlight the important role of cooperative interactions in the formation process. These combined observations point towards a ‘hidden insulating phase’ distinct from that found in the hitherto known phase diagram.